Effects of a patient’s name and image on medical knowledge acquisition - Guajardo, Jesus; Petershack, Jean; Caplow, Julie; Littlefield, John (Canadian Medical Education Journal, 2015)
Purpose: To assess whether there are differences in medical students’ (MS) knowledge acquisition after being provided a virtual patient (VP) case summary with a patient’s name and facial picture included compared to no patient’s name or image. Method: 76 MS from four clerkship blocks participated. Blocks one and three (Treatment group) were provided case materials containing the patient’s name and facial picture while blocks two and four (Control group) were provided similar materials without the patient’s name or image. Knowledge acquisition was evaluated with a multiple-choice-question examination (CQA_K). Results: Treatment group CQA_K scores were 64.6% (block one, n = 18) and 76.0% (block three, n = 22). Control group scores were 71.7%, (block two, n = 17) and 68.4% (block four, n = 19). ANOVA F-test among the four block mean scores was not significant; F (3, 72) = 1.68, p = 0.18, η2=0.07. Only 22.2% and 27.3% of the MS from blocks one and three respectively correctly recalled the patient’s name while 16.7% and 40.9% recalled the correct final diagnosis of the patient. Conclusions: These results suggest that including a patient’s name and facial picture on reading materials may not improve MS knowledge acquisition. Corroborating studies should be performed before applying these results to the design of instructional materials.